Evaluation of basal heave for deep excavation - Yang, Haiyan (2008)
The construction of basements of high-rise buildings and mass transit facilities in congested urban areas is making deep excavations more common. A safe and economic design of these excavations necessitates a thorough knowledge of the behaviour of supported excavations, particularly the bottom basal heave. Thus, this dissertation is directed toward studying the basal heave of deep supported excavations in soft clays and developing a simple method for estimating the factor of safety against basal heave associated with these excavations.